178k views
19 votes
Create an equation with one solution of x = −4. 5x − (x − 8) = 2x − ( ______ + x)

User Breandan
by
4.9k points

2 Answers

8 votes

Step-by-step explanation:

helo i had done previous one.i got 7

User Jmserra
by
4.6k points
1 vote

Answer:

Just solve the equation for the "blank space" by plugging in -4 for x. When you do this, you'll get that the "blank space" equals 4. Now just rewrite the equation as 5x - (x - 8) = 2x - (4 + x). When you solve this equation, you should get x = -4.

User Gabitoju
by
4.3k points